2021
DOI: 10.1242/jcs.251298
|View full text |Cite
|
Sign up to set email alerts
|

Turgor-dependent and coronin-mediated F-actin dynamics drive septin disc-to-ring remodeling in the blast fungus Magnaporthe oryzae

Abstract: The fungus Magnaporthe oryzae uses a specialized pressure-generating infection cell called an appressorium to break into rice leaves and initiate disease. Appressorium functionality is dependent on the formation of a cortical septin ring during its morphogenesis, but precisely how this structure assembles is unclear. Here we show that F-actin rings are recruited to the circumference of incipient septin disc-like structures in a pressure-dependent manner, and that this is necessary for their contraction and rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…Actin patches are mainly accumulated in Spitzenkörper (Spk), which is located at subapical regions of hyphal tips ( Riquelme and Sánchez-León, 2014 ); the localization of actin patches indicates their functions in endocytosis and exocytosis and involvement in hyphal tip growth ( Shaw et al., 2011 ; Takeshita et al., 2014 ). Actin cables are bundles of F-actin crosslinked by tropomyosin and fimbrin ( Evangelista et al., 2002 ); they serve as tracks for the organelle transport and secretory vesicles ( Taheri-Talesh et al., 2008 ; Berepiki et al., 2011 ; Taheri-Talesh et al., 2012 ), whereas actin rings participate in septum formation and are required for pathogenesis in Magnaporthe oryzae ( Ryder et al., 2013 ; González-Rodríguez et al., 2016 ; Dulal et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Actin patches are mainly accumulated in Spitzenkörper (Spk), which is located at subapical regions of hyphal tips ( Riquelme and Sánchez-León, 2014 ); the localization of actin patches indicates their functions in endocytosis and exocytosis and involvement in hyphal tip growth ( Shaw et al., 2011 ; Takeshita et al., 2014 ). Actin cables are bundles of F-actin crosslinked by tropomyosin and fimbrin ( Evangelista et al., 2002 ); they serve as tracks for the organelle transport and secretory vesicles ( Taheri-Talesh et al., 2008 ; Berepiki et al., 2011 ; Taheri-Talesh et al., 2012 ), whereas actin rings participate in septum formation and are required for pathogenesis in Magnaporthe oryzae ( Ryder et al., 2013 ; González-Rodríguez et al., 2016 ; Dulal et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Neurospora crassa , Aspergillus nidulans , and Colletotrichum graminicola , actin filaments form a subapical collar of actin patches, a concentration of actin at the Spk, or actin cables and patches in the hyphae (Bartnicki‐Garcia et al, 2018 ; Berepiki et al, 2010 ; Delgado‐Alvarez et al, 2010 ; Echauri‐Espinosa et al, 2012 ; Upadhyay & Shaw, 2008 ). In M. oryzae , a toroidal F‐actin ring assembles in the appressorium to facilitate breaching of the leaf surface by the rigid penetration peg (Dagdas et al, 2012 ; Dulal et al, 2021 ) and a bowl‐like actin structure capping the hyphal tip was observed during M. oryzae hyphal polar growth (Li et al, 2020 ). These observations of the diverse organization of the actin cytoskeleton in fungi provide crucial information for understanding the functions of the actin cytoskeleton in fungal development and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Much progress in recent decades has been achieved in elucidating the crucial roles of the actin cytoskeleton in fungal morphogenesis and pathogenesis, especially in M. oryzae . The M. oryzae actin motor proteins, Myosin 2 (MoMyo2) and MoMyo5, and the actin‐binding proteins, MoCap, the endocytic proteins, MoEnd3, and Coronin were reported to be key factors in M. oryzae development and virulence (Dulal et al, 2021 ; Guo et al, 2017 ; Li et al, 2017a , 2017b ; Motaung & Tsilo, 2017 ; Tang et al, 2018 ). In addition, septin proteins, which scaffold cortical F‐actin at the point of plant infection in the M. oryzae appressorium, provide cortical rigidity for physically rupturing the leaf cuticle (Dagdas et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations